Costs of pharmacotherapy in pediatric patients with community-acquired pneumonia: mathematical and statistical analysis - I. A. Narkevich; O. D. Nemyatyh; D. D. Siukaeva; I. V. Pavlushkov; D. O. Ivanov; Ya. V. Panyutina (IRBIS LLC, 2019)
The aim of the study is to determine the limits of using the mathematical-statistical analysis for the evaluation of pharmacotherapy costs in pediatric inpatients diagnosed with community-acquired pneumonia. Materials and methods. The report is based on the assessment of 547 medical records of patients with community-acquired pneumonia, who underwent the treatment in four pediatric hospitals in St. Petersburg. The data array was created from a number of factors that characterize the patients' profile (gender, duration of hospital stay, cost of therapy, number of prescribed drugs, number of affected lung segments, pathogen location, leukocyte count, and eSR). Results. Correlation analysis allowed us to identify factors contributing to the cost of pharmacotherapy (at a significance of p=0.05); those were: the duration of hospital stay (r=0.34), the number of prescribed drugs (r=0.26), and the number of affected lung segments (r=0.21). Dispersion analysis of qualitative factors (gender, location of pneumonic infiltrate) showed no significant impact of these factors on the costs or the number of prescribed drugs in the total data set. From the regression analysis, we obtained formulas for the dependence of the resulting parameters (cost of pharmacotherapy, number of prescribed drugs) on a set of independent variables. Conclusion. The treatment cost optimization in pediatric patients with community-acquired pneumonia should include the use of antibacterial drugs with proven efficacy and safety, as well as a reduction in non-necessary supporting therapy, e.g., medications aimed to correct morphological and functional changes in the respiratory system.